Teaching resources for teaching the history of philosophy (2015)
The concern of teachers for teaching philosophy has been incessant, so that we have designed a proposal that addressed the process from the teaching philosophy of secondary education. Research from the classroom seeks knowledge to solve problems of teaching the history of philosophy and philosophical authors of every age and schools, through games like: philosophical parks, Poker, Keno, Chess, Tasos, Monopoly, rich uncle, Album, philosophical Dictionary, Bingo, Bulletin, Stairs, Domino, Videos; among others in order to develop their creative, methodical, reasoned, orderly, abstract, meditative, deliberative and speculative thought. Developing teaching resources for teaching the history of philosophy has become an experience of successful character has also been innovative as it has helped students of different levels to respond effectively to academic life and the examination of Saber 11th. Therefore the research question is: What educational improvement strategy could arise for the philosophical training of high school students to qualify their learning and comprehensive training?